Soil residues of sulfosulfuron herbicide in wheat field determined by bioassay and laboratory methods - Alireza Kazemi; Mehran Hoodaji (Plant, Soil and Environment, 2022)
Although herbicides are used for weed control in the field, their residues can have unfavourable environmental impacts. The objective was to determine the sulfosulfuron herbicide residues in wheat field soil using bioassay and laboratory (HPLC) methods. The two-year experiment was a randomised complete-block design (RCBD) with three replicates using herbicide at control, recommended (26.6 g/ha, D1) and doubled (53.2 g/ha, D2) rates. Soil samples (0-10 cm) were collected randomly at intervals ranging from 0 to 125 days after spraying. Greenhouse experiments (bioassay method) with eight plant species indicated garden cress (Lepidium sativum L.) and corn (Zea mays L.) as the most and the least sensitive ones, respectively. The herbicide residues were stable at D1 up to 90 days after herbicide use, at 1.41 and 0.52 μg/kg in 2019 and 2020, respectively. However, 125 days after herbicide use no residues were observed. With time and for both treatments, soil herbicide residues decreased or the percentage of herbicide loss increased. The sensitivity of HPLC method to detect the herbicide residues was less than the bioassay method. The three-parameter sigmoid equation indicated the mean of DT50 for D1, averaged for the two years it was 19 days.